2010
DOI: 10.1016/j.pain.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous C-fiber nociceptor responses and nociceptive behaviors in aged Sprague–Dawley rats

Abstract: The change with age in pain perception in humans and the nociceptive behaviors in animals elicited by noxious stimuli to the skin are not well understood, and little is known about the peripheral neural mechanisms of cutaneous nociception in the aged. We systematically examined cutaneous nociceptor responses and nociceptive behaviors in young (9-14 w) and in aged (127-138 w) Sprague-Dawley rats. C-fiber nociceptors in the skin were identified by mechanical and electrical stimulation, and extracellularly record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 26 publications
4
49
2
Order By: Relevance
“…Since previous studies showed no significant age-related differences in withdrawal latency to hot temperatures 32 and mechanical stimuli 42 in adult rats, the end point of shamoperated rats was determined at 5 weeks postoperatively. In addition, as part of unpublished experiments, we have examined 3 sham-operated rats for behavioral but mainly for possible age-related changes in histological data at 30 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies showed no significant age-related differences in withdrawal latency to hot temperatures 32 and mechanical stimuli 42 in adult rats, the end point of shamoperated rats was determined at 5 weeks postoperatively. In addition, as part of unpublished experiments, we have examined 3 sham-operated rats for behavioral but mainly for possible age-related changes in histological data at 30 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…An activity-dependent change in conduction velocity (ADCCV) index was used for the single-fibers electrically identified in series 1. The methods used to obtain this index have been established in our previous report with the skin-nerve preparations, 53 but not with the muscle-nerve preparations.…”
Section: Axonal Conductive Properties Of Cutaneous C-nociceptorsmentioning
confidence: 99%
“…Rat hindpaw skin-saphenous nerve preparation was used, and the methods of recording single fiber activities, stimulation of the fibers and data analysis were basically the same as previously reported (Banik et al, 2001;Taguchi et al, 2010). Briefly, the skin from one or both hindlimbs was carefully removed with the saphenous nerve attached after CO 2 euthanasia.…”
Section: Electrophysiological Recordings Of Single Afferent Fibersmentioning
confidence: 99%
“…We used the same response criteria as in our previous study with cutaneous afferents to determine whether a fiber was responsive to a stimulus (Taguchi et al, 2010). Specifically, a fiber was defined to be sensitive to mechanical stimulation when it fulfilled the following criteria: (1) the net increase in the discharge rate during the stimulus period was more than 0.1 imp/s over the background discharge rate (BDR) during the control period of 60 s immediately before the onset of the mechanical stimulus, and (2) the instantaneous discharge rate of two consecutive discharges exceeded the mean + 2 SD of the BDR.…”
Section: Mechanical Stimulation (Pressing the Receptive Field)mentioning
confidence: 99%